PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) PADA MATERI PERUBAHAN LINGKUNGAN UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN HASIL BELAJAR KOGNITIF - Wardatul Maufiroh; Isnawati Isnawati; Siti Kurnia (Jurnal Ilmiah Global Education, 2023)
This study aims to determine the learning motivation and cognitive learning outcomes of students in the subject of environmental change using the problem-based learning (PBL) method. This type of research is Classroom Action Research (CAR) with 2 cycles. Each cycle consists of the stages of planning, implementing actions, observing, and reflecting. The subjects in this study were students of SMAN 1 Kamal class X-6 with a total of 36 students. Data was collected using observation, interviews, questionnaires, and test questions. The instruments used were questionnaire sheets and multiple-choice test sheets, which were then analyzed using quantitative descriptive analysis techniques. The results of the study show that the use of problem-based learning (PBL) models on environmental change material can increase learning motivation and cognitive learning outcomes of students. The percentage of students' learning motivation towards learning through the PBL model in cycle 1 with the very good category was 2.78%, the motivation to learn in the good category was 52.78%, and the sufficient category was 44.44%. In cycle 2 there was an increase in the very good learning motivation category by 11%, the good category by 75%, and the sufficient category by 14%. The percentage of cognitive learning outcomes of students who met KKM standards in cycle 1 was 69.44% and increased in cycle 2 by 86%.